2011
DOI: 10.1371/journal.ppat.1002288
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Proliferation Fails to Efficiently Reactivate HIV-1 Latently Infected Central Memory CD4+ T Cells

Abstract: Homeostatic proliferation ensures the longevity of central memory T-cells by inducing cell proliferation in the absence of cellular differentiation or activation. This process is governed mainly by IL-7. Central memory T-cells can also be stimulated via engagement of the T-cell receptor, leading to cell proliferation but also activation and differentiation. Using an in vitro model of HIV-1 latency, we have examined in detail the effects of homeostatic proliferation on latently infected central memory T cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 35 publications
11
152
0
1
Order By: Relevance
“…We observed that treatment with bryostatin alone led to significant decreases in both levels of HIV DNA and IUPM (Supplemental Figure 3, P < 0.0001 and P = 0.003, respectively). This is consistent with previous studies, which have indicated that potent LRAs alone are sufficient to drive some elimination of infected cells in this and other models of latency (5,32). As expected, substantially greater reductions in levels of both HIV DNA and IUPM were observed following combination treatment with bryostatin and ABT-199 (Supplemental Figure 3, P = 0.0009 and P < 0.0001, respectively, compared with bryostatin alone).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that treatment with bryostatin alone led to significant decreases in both levels of HIV DNA and IUPM (Supplemental Figure 3, P < 0.0001 and P = 0.003, respectively). This is consistent with previous studies, which have indicated that potent LRAs alone are sufficient to drive some elimination of infected cells in this and other models of latency (5,32). As expected, substantially greater reductions in levels of both HIV DNA and IUPM were observed following combination treatment with bryostatin and ABT-199 (Supplemental Figure 3, P = 0.0009 and P < 0.0001, respectively, compared with bryostatin alone).…”
Section: Resultssupporting
confidence: 92%
“…We therefore moved to the use of CD8 + T cell clones to define the potential roles of immune escape and effector function in our observations. Before applying this assay to ex vivo CD4 + T cells, we performed validation experiments on a primary cell model of postactivation latency (32,33) to determine whether it could reliably measure changes in levels of both HIV DNA and IUPM. Infected cells of this latency model were spiked into autologous ex vivo CD4 + T cells to generate target cell populations, approximating the infected cell frequencies found in patient samples.…”
Section: Resultsmentioning
confidence: 99%
“…Whether the efficacy of viral reactivation in functionally polarized cells is influenced by signature transcription factors of polarized T cells is currently unknown; however, it is noteworthy that GATA-3 and c-Maf, two transcription factors involved in regulating Th2-polarization, can stimulate HIV-1 expression through direct interactions with the HIV-1 promoter (28,29); this may facilitate immune-mediated clearance of HIV-1-infected Th2 cells and correspond to the very low frequency of clonally-expanded Th2 cells encoding intact HIV-1 in our study. Interestingly, TCR-independent homeostatic proliferation can drive HIV-1-infected cell proliferation in the absence of viral reactivation (30), at least in in vitro experiments, but this mechanism may possibly account for a smaller proportion of clonal turnover in T cells, relative to antigen-driven T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…There was a progressive decrease in p24 Gag staining at days 5 and 7 after infection. This decrease in productively infected cells was previously shown to be due to cellular apoptosis (39). Infected cultures were maintained in medium containing recombinant IL-2 (rIL-2) for 9 days postinfection, allowing the cells to naturally revert to a quiescent state and acquire a central-memory phenotype.…”
Section: Expression Of P-tefb In Naïve and Central Memory Cd4mentioning
confidence: 99%